Nestwork new material rhetorics for precarious species - Clary-Lemon, Jennifer (RSA series in transdisciplinary rhetoric., 2023)
"Examines how humans interact with small, uncharismatic species through three rhetorical case studies of human responses to bird species decline that challenge anthropocentric models of rhetoric"--